Changes in the life style, needs and difficulties faced by caregivers of aids patiens in home care - Gir, Elucir; Reis, Renata Karina (Revista da Escola de Enfermagem da USP, 2001)
This study aimed at delineating the social and demographic profile of 17 home caregivers for AIDS patients, identifying the alterations occurring in their life style and detecting the main needs and doubts presented by them when assisting a person living with AIDS at home, as well as the difficulties stemming from the disease and the care givén by them. We identified that the introduction of HIV/AIDS within the family generates a crisis situation and awakens many negative feelings in caretakers. An alteration in life routine takes place and there is also an overload of tasks to be carried out. The main difficulties of caretakers are related to taking care of the patient at home in addition to financial and emotional difficulties. We have shown the need for more effective orientation as to protection measure while caring for the patient. We have also pointed out the importance of orientation and educational actions to be given by health professionals, during which nurses' participation in home assistance/visits is essential.